Cinzia Vismara, Maria Letizia Caldelli: Epigrafia anfiteatrale dell’Occidente Romano V. Alpes Maritimae, Gallia Narbonensis, Tres Galliae, Germaniae, Britannia, 2000 - Šašel Kos, Marjeta (Arheološki vestnik, 2002)
.